(untitled) (AYUSHDHARA, 2023)
The combination of obesity, dyslipidaemia, impaired glucose tolerance, hypertension often combined to the term ‘Metabolic Syndrome’ affects nowadays approximately more than 30% of the population of young generation. It has become a significant global health challenge associated with an increased risk of atherosclerotic cardiovascular disease (CVD). Ayurveda provides insights into the understanding of Metabolic Syndrome through concepts like Medodhatuvriddhi, Medovahasrothodushti, Santharpanajanya vikara (Sthoulya, Medoroga, Prameha, Hrdroga) and Amapradoshaja vikara. The aim of the study is to evaluate the efficacy of Huthabhugadi Churna and Trayushnadi Ghrtam as an Ayurvedic protocol in metabolic syndrome. This study is a case series done on 5 subjects, were Huthabhugadi Churna 6gm twice daily before food with Takra as Anupana was given for 14 days followed by Trayushnadi Ghrtam 5gm thrice daily with lukewarm water as Anupana next 14 days. Assessment was done on 0th day, 29th day and 42nd day with subjective and objective parameters. The Kapha vatahara and Medohara properties of trial drugs helped in the elimination of excess Medodhathu and formation of optimal Rasadi dhathus relieving the symptoms associated with metabolic syndrome The study showed a significant effect in normalising the lipid profile and improving the quality of life. These findings challenge the common misconception that consuming ghee leads to hyperlipidaemia offering valuable insights for further research and validation.